Gender Differences in the Clinical Characteristics of Patients with Acute Coronary Syndrome in the Eastern Region of Nepal - Dhungana, Sahadeb Prasad; Adhikari, Roshna; Khatiwada, Sameen (Journal of Nobel Medical College, 2020)
Background: Studies from other regions show gender-based differences in the clinical characteristics of patients with the acute coronary syndrome (ACS) with conflicting results. There is a lack of definite data from our population. Materials and Methods: This is a hospital-based cross-sectional study in patients with ACS admitted to the tertiary care center from January 2019 to June 2020. Risk factors, co-morbidities, clinical symptoms, duration of symptoms onset, modalities of treatment offered, complications, and in-hospital outcome were noted in the pre-structured questionnaire by convenient sampling. Data were analyzed by using Microsoft excel 2007 and SPSS 20. Results: Among 384 participants, 65.9% were male and 34.1% were female. The mean age of males was 60.6 ± 12.1 and females 62.3 ± 11.1 years (P=0.21). Females had a higher prevalence of dyslipidemia (p<0.001). The prevalence of hypertension, diabetes, and smoking was similar. The mean hemoglobin level was higher in males (11.8 ± 2.2 gm/dl vs. 11.1 ± 4.57 gm/dl, P = 0.01). The majority presented with chest pain (94.9%) in males and 87.8% in females, P=0.44), and sweating (76.7% in males and 80.2% in females, P=0.43). Non-anginal symptoms were almost similar in both the genders except nausea which was more common in males (P=0.03). The timing of presentation, treatment with reperfusion therapy, and arterial territory involved were not significantly different. Prevalence of mechanical and arrhythmic complications as well as mortality was similar. Conclusion: Our study did not show significant gender-based differences in clinical profile, treatment modalities, in-hospital complications, and mortality.